Digital Transformation in Public Administration as a Means to Achieve Efficiency and Sustainability A Case Study in the Baghdad Municipality - فتاح ابتسام احمد (Tasnim International Journal for Human, Social and Legal Sciences, 2026)
In the near future, public administration will witness a qualitative transformation through the adoption of digitalization as a central tool for resource management and decision-making. This transformation will not be merely a technical update; rather, it will represent a cultural shift in the concept of efficiency and sustainability in the government sector. This research aims to explore the impact of digital transformation in public administration on improving institutional efficiency and enhancing operational sustainability. The importance of this research stems from the urgent need for more flexible and effective government institutions capable of keeping pace with the rapid changes in the work environment. The research problem is the weak digital integration in some public administrations, which leads to slow procedures and a decline in the quality of public services. Hence, the research poses the main question: How does digital transformation in public administration contribute to achieving efficiency and sustainability? The main hypothesis is that the introduction of digital transformation systems in public administration will lead to increased operational efficiency and enhance opportunities for long-term sustainability. The research is limited to local public administrations, focusing on the direct and indirect effects of digital transformation. The study will be applied practically in the Baghdad Municipality Department to a community of public administration workers, with a sample of (50) employees representing various functional and administrative levels. The research relies on a descriptive analytical approach using questionnaires to collect and analyze data. The results are expected to confirm the positive relationship between digital transformation and increased efficiency by reducing time and cost and improving service quality, as well as enhancing sustainability by reducing waste and relying on smart systems in resource management. The study recommends the formulation of an integrated national strategy for digital transformation, including continuous employee training, modernizing the technical infrastructure, and adopting policies that encourage government innovation to ensure the success of this transformation and achieve sustainable development goals.